Economic Empowerment through Muhammadiyah-Owned Enterprises A Case Study of Muhammadiyah Regional Board of Lumajang - Imamul Hakim; Muhammad Sarif; Aunur Rofiq (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2022)
This article examines the Muhammadiyah-Owned Enterprises (Badan Usaha Milik Muhammadiyah (BUMM)) managed by CV. Syirkah Amanah and its role in the economic Empowerment of Muhammadiyah organizations and the community. CV. Syirkah Amanah is the research object because it has shown exemplary  achievements in managing BUMM. This study uses a qualitative descriptive approach with data sources through interviews, document reviews, and field observations. This study indicates that the management and development of business units owned by Muhammadiyah organizations have a significant role in the organization’s economicEmpowerment and community economic empowerment. In empowering the community’s economy, namely the existence of new job opportunities, invest and increase financial income. Meanwhile, in empowering the organization’s economy, namely increasing financial resources for the sustainability of organizational activities and increase the development of social service facilities in carrying out the organization’s vision and mission.